On the Use of Portfolio Risk Models and Capital Requirements in Emerging Markets : The Case of Argentina - Balzarotti, Veronica; Falkenheim, Michael; Powell, Andrew (Washington, DC: World Bank, 2014)
A portfolio based model (Credit Risk of Credit Suisse First Boston) and recent Central Bank of Argentina credit bureau data are used to estimate whether current capital and provisioning regulations match actual risks. Arguing that provisions should cover expected losses and that capital requirements should cover potential losses beyond expected losses subject to some statistical level of tolerance, the article assesses how well actual capital and provisioning requirements match the estimated requirements given by the model. Actual provisioning requirements were found to be close to implied levels of expected losses. The estimate of potential losses was found to be highly sensitive to the assumptions of the model, especially the parameter relating the volatility of a loan's rate of default to its mean value. This volatility parameter cannot be estimated accurately with the credit bureau data because of the short time span covered, so proxy data were used to estimate it, and two values around that estimate were tried. The difficulty of estimating this critical parameter implies that the results should only be regarded as suggestive. Moreover, the methodology only does not seek to estimate credit risk and not interest rate risk or exchange rate risk, nor does it fully take into account the indirect effects of interest rates and exchange rates on credit risk. As recent events in Argentina have demonstrated, estimating credit risk along these lines should be thought of as just one tool in attempting to assess the appropriate level of bank provisions and capital.